Republic of Estonia : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
This 2004 Article IV Consultation highlights that economic activity has been gathering speed in Estonia. Year-over-year growth accelerated to 6.8 percent in 2004 Q1 from 5.8 percent in 2003 Q1, driven by domestic demand and supported by technology sector exports. Inflation accelerated in the first half of 2004 as a result of European Union tax harmonization. Estonia's banking system remains financially sound. The percentage of nonperforming loans declined further and, at 0.4 percent of the total, is the lowest among transition countries.